Gastric villous polyp - Gastambide, Carmelo; Estrugo, Roberto; Croci, Fabio; Calleriza, Fernando (Cirugía del Uruguay, 1983)
We have seen one case of a gas_tric polyp; therapeutical, pathological and clinical considerations were made. Its higb. lncidence of mall.gnant potential is emphasized. A bibliographic review is made.